Characteristics of costume design in children's theater performances (Al-Academy, 2022)
Theatrical costume constitutes a peculiarity in the theatrical performance because of its ability to communicate and communicate with the rest of the visual elements of the show in highlighting the intellectual and dramatic values. Fashion developments in theatrical performance, the second: the design elements of costumes and their characteristics, the third, which includes research procedures, and the fourth, in which the research results and conclusions were presented, including:The play (Happening on the Farm) is considered one of the plays with educational, educational and aesthetic goals, as it carried in its formats the features of simplicity and diversity of the visual formal connotations of the child.The costume designer has an important role in communicating the idea of ​​the play and its contents and conveying its connotations as well as his imaginative and innovative ability, by dealing with the nature of the material or material and designing it in accordance with the viewers of the show. The study concluded with sources and appendices.